Experimental investigation of MnFeP1−xAsx multilayer active magnetic regenerators. (14th July 2017) - Govindappa, P; Trevizoli, P V; Campbell, O; Niknia, I; Christiaanse, T V; Teyber, R; Misra, S; Schwind, M A; van Asten, D; Zhang, L; Rowe, A
Abstract: This paper describes experimental performance data for MnFeP1− x As x multilayer active magnetic regenerators. Five different matrices are tested: (i) one with three layers; (ii) one with six layers; and (iii) three, eight-layer regenerators where the layer thickness is varied. The tests are performed using a dual regenerator bespoke test apparatus based on nested Halbach permanent magnets. (PM II test apparatus at the University of Victoria.) Operating variables include displaced volume (3.8–12.65 cm 3 ), operating frequency (0.5–0.8 Hz) and hot-side rejection temperature (293–313 K). The results are mainly reported in terms of zero net load temperature span as a function of rejection temperature; a few tests with non-zero applied load are also presented. A maximum temperature span of 32 K is found for an eight-layer regenerator, which is similar to a previous work performed with gadolinium in the same experimental apparatus.